The effect of temperature on pyrolysis products during oil shale thermal decomposition - Fajun Zhao; Zian Yang; Lei Zhang; Changjiang Zhang; Tianyu Wang; Hong Zhang (Scientific Reports)
Abstract This study systematically investigates the effect of temperature on product distribution and reaction mechanisms during the pyrolysis of oil shale through thermogravimetric analysis (TG) and fixed-bed pyrolysis experiments. The results indicate that the oil shale pyrolysis process can be divided into three stages: the low-temperature stage, dominated by water evaporation; the mid-temperature stage (400–650 °C), which is the primary stage for organic matter decomposition; and the high-temperature stage (> 650 °C), characterized by secondary cracking of heavy components and decomposition of mineral residues. The study reveals that temperature significantly influences the generation and distribution of gas, liquid, and solid products. Gas yield increases markedly under high-temperature conditions, especially for H2 and CH4. The shale oil yield reaches its peak at mid-temperatures (400–500 °C), but decreases at higher temperatures due to secondary cracking reactions. The fixed carbon content of the semi-coke decreases with increasing temperature, while the mineral components decompose into porous oxides at high temperatures. Kinetic analysis demonstrates that primary reactions drive the mid-temperature pyrolysis, whereas secondary reactions enhancing gas production become dominant at high temperatures. This study elucidates the regulatory mechanisms of temperature on oil shale pyrolysis behavior, providing guidance for the targeted optimization of specific products, such as gases, shale oil, or semi-coke. The findings offer scientific and technical references for optimizing pyrolysis processes and improving the efficient utilization of unconventional energy resources.